Identifikasi Penerapan ERP dan Resiko Managemen Pada RSUD Dr Samratulangi Tondano Kabupaten Minahasa Sulawesi Utara - Rumambi, Frendy Rocky; Amalia, Citra; Alexander, Rully (Universitas Diponegoro, 2018)
Influential information technology in all areas of one field of health evidenced denganteknologi can help health services in the form of examination, diagnosis, treatment, and decision making. The role of information technology in the sphere of kesehatandapat providing services and address the risks. The purpose of this research is to study how the application of ERP and risk management at hospital. It was concluded that an ERP system successfully applied in the field of health there are risks regarding the service. ERP systems can improve health services. The lack of research in this field, furthermore investigates the use of ERP in the field of health and the application of risk management. conclusion, used system ERP at the hospital has not been applied as a whole, many clinical functions as well as a database on the health section at the hospital have not yet integrated, sistemhanya focuses on the function of registration and administration comparison of clinical function, there are many risks facing health care providers especially about service. Factor in the availability of technology and human resources to the implementation of the ERP system and risk management